Network Formation via Anion Coordination: Crystal Structures Based on the Interplay of Non-Covalent Interactions - Matteo Savastano; Carla Bazzicalupi; Palma Mariani; Antonio Bianchi (Molecules, 2018)
We describe the synthesis and the structural characterization of new H2L(CF3CO2)2 (1) and H2L(Ph2PO4)2 (2) compounds containing the diprotonated form (H2L2+) of the tetrazine-based molecule 3,6-di(pyridin-4-yl)-1,2,4,5-tetrazine. X-ray diffraction (XRD) analysis of single crystals of these compounds showed that H2L2+ displays similar binding properties toward both anions when salt bridge interactions are taken into account. Nevertheless, the different shapes, sizes and functionalities of trifluoroacetate and diphenyl phosphate anions define quite different organization patterns leading to the peculiar crystal lattices of 1 and 2. These three-dimensional (3D) architectures are self-assembled by a variety of non-covalent forces, among which prominent roles are played by fluorine–π (in 1) and anion–π (in 2) interactions.